The CHAMÍ System to Assist the Quality Assurance of Functional and Non-Functional Requirements in the Software Industry (2022)
This article aims to propose a model for quality assurance of functional and non-functional requirements in Software Projects that may be appropriate for the MSME industry and find a propitious scenario to improve its competitiveness in the national and international order based on the products it manufactures. The metamodel was validated from its conceptualization, development, implementation, and evaluation with experts from academia and industry to reduce the gap between them. As a result, the development of an information system adjusted to the needs of regional software producers is achieved, which has the ability to accompany software projects in the management of quality requirements from the first stages, in accordance with the quality characteristics established by international organizations with experience in the discipline.